2001
DOI: 10.1034/j.1399-3011.2001.00899.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel cyclic peptide inhibits intercellular adhesion molecule‐1‐mediated cell aggregation

Abstract: Leukocyte adherence mediated by intercellular adhesion molecule-1 (ICAM-1) binding to leukocyte function-associated antigen (LFA-1) is required for proper inflammatory and immune function. Inhibition of ICAM-1\LFA-1 binding using monoclonal antibodies (mAb) has been shown to be efficacious at inhibiting lymphoma metastasis as well as leukocyte emigration into tissue in a number of inflammatory diseases such as ischemia-reperfusion injury, septic shock and rheumatoid arthritis. In this report, we describe the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…Furthermore, peptides can act as lead compounds by providing a structural basis for the identification of nonpeptide mimetics when oral availability and increased potency are required. Peptides have been identified that can inhibit a number of cellular targets, including angiotensin-converting enzyme 2 (17), melanoma inhibitor of apoptosis (8), vascular endothelial growth factor (14), and intracellular adhesion molecule 1 (44), to name but a few. Likewise, in addition to a large number of naturally occurring antimicrobial peptides, a number of additional peptides, either novel or based on cellular components, have been identified, including a 36-amino-acid peptide called enfuvirtide (Fuzeon; Roche) currently marketed to prevent HIV-1 infection of T cells (7,27).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, peptides can act as lead compounds by providing a structural basis for the identification of nonpeptide mimetics when oral availability and increased potency are required. Peptides have been identified that can inhibit a number of cellular targets, including angiotensin-converting enzyme 2 (17), melanoma inhibitor of apoptosis (8), vascular endothelial growth factor (14), and intracellular adhesion molecule 1 (44), to name but a few. Likewise, in addition to a large number of naturally occurring antimicrobial peptides, a number of additional peptides, either novel or based on cellular components, have been identified, including a 36-amino-acid peptide called enfuvirtide (Fuzeon; Roche) currently marketed to prevent HIV-1 infection of T cells (7,27).…”
Section: Discussionmentioning
confidence: 99%
“…The peptides that we identified in this study may serve as lead compounds for further optimization. The optimization of peptide antagonist activity through alanine and homologous amino acid substitution has resulted in 2-to 3-log improvements in inhibitory activity in other systems and may be justified in this system as well (35,37). Finally, structural information about peptides may be used as a guide to create orally available nonpeptide organics.…”
Section: Vol 79 2005 Peptide Inhibitors Of Snv Entry 7323mentioning
confidence: 99%
“…In fact, 10 of 11 peptides (group 4) with the greatest inhibition of SNV infectivity did not have significant sequence relatedness to SNV glycoproteins. Identification of inhibitory peptides that do not have significant sequence relatedness to native ligands has been described in other systems (35)(36)(37), and a large amount of work has indicated that nonhomologous amino acids may mimic the binding activities of each other (reviewed in reference 35). In addition, a comparison of the peptide sequences homologous with SNV to HTNV and PHV glycoproteins did not clearly identify possible contact points of FIG.…”
Section: Vol 79 2005 Peptide Inhibitors Of Snv Entry 7323mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, identification of cell surface adhesion molecules that mediate the adhesion of leukocytes to the endothelium, such as leukocyte functional antigen-1 (LFA-1) and its ligand intercellular adhesion molecule-1 (ICAM-1), have allowed investigation into leukocyte trafficking [3][4][5]. Collaborators at the University of New Mexico Health Sciences Center developed a novel antagonist of ICAM-1 that has in-vivo efficacy [6][7][8][9], and Kelly and coworkers [10,11] have developed a small molecule antagonist of LFA-1, although toxicity effects have limited its development as an in-vivo inhibitor. Using our technique, we can predict compounds that provide the proper inhibitory effect, some of which hopefully lack any adverse toxicity effects.…”
Section: Introductionmentioning
confidence: 99%